2020
DOI: 10.1016/j.jaci.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bcl6 and Blimp1 reciprocally regulate ST2+ Treg–cell development in the context of allergic airway inflammation

Abstract: Background: Bcl6 is required for the development of T follicular helper and regulatory (Tfh, Tfr) cells that regulate germinal center responses. Bcl6 also impacts the function of regulatory T (Treg) cells. Objective:The goal of this study is to define the functions of Bcl6 in Treg cells including Tfr cells in the context of allergic airway inflammation (AAI). Methods: We employed a model of house dust mite (HDM) sensitization to challenge wild type, Bcl6 fl/fl Foxp3-Cre and Prdm1(Blimp1) fl/fl Foxp3-Cre mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 73 publications
(78 reference statements)
1
37
0
Order By: Relevance
“…Rivas et al found that enhancing IL-4R-STAT6 signaling decreased the formation of allergen-specific Treg in food allergy model 11 . IL-4 secreted by Th2 is enriched in allergic asthma 12 and are potent at promoting allergic inflammation 13 . However, the underlying mechanisms of IL-4 repressing Treg differentiation have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Rivas et al found that enhancing IL-4R-STAT6 signaling decreased the formation of allergen-specific Treg in food allergy model 11 . IL-4 secreted by Th2 is enriched in allergic asthma 12 and are potent at promoting allergic inflammation 13 . However, the underlying mechanisms of IL-4 repressing Treg differentiation have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…62 Although no direct signalling pathway has been proposed, this suggests Blimp-1 functions downstream of ST2, which is in sharp contrast to cells in the T-cell lineage mentioned above. 37,38…”
Section: Blimp-1 In Mononuclear Phagocytic Developmentmentioning
confidence: 99%
“…Likewise, Blimp‐1 can stabilize the suppressive phenotype and correct localization of follicular Tregs, allowing them to inhibit germinal centre reactions 36 . However, the role of Blimp‐1 in follicular Tregs may be context‐dependent, as Blimp‐1 expression induces an ST2 + (Il1rl1, IL‐33R) allergy‐promoting phenotype of Tregs in the house dust mite model of allergic asthma 37 . Interestingly, Blimp‐1 shows particularly high expression levels in visceral adipose tissue Tregs in male mice, where it is induced in response to, and is essential to counteract, the low‐grade inflammatory signals sent by male visceral stroma.…”
Section: Blimp‐1 Is Broadly Expressed and Fulfills Many Different Romentioning
confidence: 99%
See 2 more Smart Citations